On linear spectral transformations and the Laguerre–Hahn class. Issue 11 (2nd November 2017) - Castillo, K.; Rebocho, M. N.
ABSTRACT: We study the Christoffel and Geronimus transformations for Laguerre–Hahn orthogonal polynomials on the real line. It is analysed the modification on the corresponding difference-differential equations that characterize the systems of orthogonal polynomials and the consequences for the three-term recurrence relation coefficients.